2008
DOI: 10.1128/iai.01330-07
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cereusInduces Permeability of an In Vitro Blood-Retina Barrier

Abstract: Most Bacillus cereus toxin production is controlled by the quorum-sensing-dependent, pleiotropic global regulator plcR, which contributes to the organism's virulence in the eye. The purpose of this study was to analyze the effects of B. cereus infection and plcR-regulated toxins on the barrier function of retinal pigment epithelium (RPE) cells, the primary cells of the blood-retina barrier. Human ARPE-19 cells were apically inoculated with wild-type or quorum-sensing-deficient B. cereus, and cytotoxicity was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 64 publications
7
33
0
Order By: Relevance
“…When analyzed by Western, ZO-1 expression was not detected and occludin expression was <5% by 12 h postinfection. Retinal occludin signal was lost more rapidly than ZO-1 during early infection, corroborating similar findings in RPE monolayers in vitro 13. ZO-1 and occludin were detected at 12 h postinfection via immunohistochemistry, but signals were intermittent.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…When analyzed by Western, ZO-1 expression was not detected and occludin expression was <5% by 12 h postinfection. Retinal occludin signal was lost more rapidly than ZO-1 during early infection, corroborating similar findings in RPE monolayers in vitro 13. ZO-1 and occludin were detected at 12 h postinfection via immunohistochemistry, but signals were intermittent.…”
Section: Discussionsupporting
confidence: 85%
“…Because in vitro data suggested that plcR- deficient B. cereus induced permeability of polarized RPE monolayers similarly to that of wild-type B. cereus ,13 we analyzed whether plcR- deficient B. cereus induced leakage of fibrin across the BOB during experimental B. cereus endophthalmitis. Histological analysis by trichrome staining demonstrated fibrin leakage into the anterior and poster chambers by 8 h, with similar dispersal throughout the eye by 12 h postinfection (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…66 Recent findings have demonstrated that RPE plays a crucial role during infection by secreting cytokines like IL-6 and controlling the blood-retinal barrier. 67 As they constitute the outer blood-retinal barrier, they may be providing the first line of defense in endogenous endophthalmitis, where the pathogens are entering the retina via the choroid. Although, the incidence of endogenous endophthalmitis is relatively low, it is very common in immune-compromised individuals like diabetics.…”
Section: Retinal Innate Immunitymentioning
confidence: 99%